The Degree of Chemistry Teachers Practicing Creative Thinking Skills from their Point of View (International Journal of Psychosocial Rehabilitation, 2020)
The current study aims to know the degree of chemistry teachers at the secondary stage in the skills of creative thinking from the viewpoint of the teachers themselves, who are affiliated with the third Baghdad/Karkh Education Directorate. The two researchers used the descriptive approach, and a special questionnaire was prepared consisting of four main skills (fluency, flexibility, originality, and revelation), and 20 sub-skills were included under it. The validity and consistency of the tool were verified, and the results concluded that the degree of chemistry teachers practicing creative thinking skills is high. The researchers proposed a set of proposals, including conducting other studies to find out the degree to which chemistry teachers possess creative thinking skills from the point of view of their supervisors and to make a comparison between the results of the current study and the proposed study.